Theory of coevolution of cytoplasmic male-sterility, nuclear restorer and selfing. (21st September 2019) - Yamauchi, Atsushi; Yamagishi, Takahiro; Booton, Ross; Telschow, Arndt; Kudo, Gaku
Highlights: We theoretically investigated gynodioecy, i.e., a coexistence of hermaphroditic and female individuals in a plant population, focusing on an inter-genomic conflict. Mitochondria can result in cytoplasmic male sterility (CMS), whereas nucleus evolves abilities of male restoration and self-fertilization. If selfing of hermaphroditic individuals reduces a pollen supply to female individuals, it may suppress CMS evolution. Analysis of coevolution showed that when a high level of selfing rate evolves, CMS and/or restoration tend to decline, which might support our hypothesis. We also indicated multi-stabilities of reproductive modes and selfing rates in the system. Abstract: Gynodioecy is a sexual polymorphism in angiosperms, where hermaphroditic and female individuals coexist. This is often caused by a cytoplasmic genetic element (CGE) that destroys male functions, which is called cytoplasmic male-sterility (CMS). On the other hand, nuclear genes tend to evolve the ability to restore male function. The coevolutionary process of CMS and the restoration has been studied theoretically. Recently, a theoretical study suggested that these coevolutionary dynamics could be influenced by the rate of selfing within populations, although it assumed that the selfing rate of a population was a fixed parameter. Accordingly, we theoretically study the coevolution of three traits in this paper: CMS, nuclear restorer and selfing rate, in which we hypothesize that selfing evolution can suppress CMS evolution under some conditions. The analysis indicates three significant properties of the system; (1) CMS-restorer evolution can result in bistability under a given selfing rate, (2) the coevolution of three traits can realize intermediate levels of selfing, and (3) the evolution of high levels of selfing is conditionally associated with no CMS and/or no restoration, which may support our hypothesis.